Academic dishonesty among accounting students in Malaysia - Yussof, Salwa Hana; Ismail, Suhaiza (Accounting Research Institute (ARI), 2018)
There are three objectives of the present study: to ascertain the types of assessment which are subject to cheating by accounting students; to determine the justifications given by students in neutralizing their cheating behavior; and to identify cheating deterrents from the perception of the students. A total of 435 questionnaires were collected from undergraduate accounting students of all levels of study in a public university in Malaysia. Findings revealed that more than half of the respondents had engaged in cheating, but mainly in quizzes and assignments that offer less weighting towards a final grade, and were subject to less monitoring and less severe punishment. As for neutralization, those who cheated had a tendency to blame instructors for their cheating behavior. In terms of deterrence, religion was cited most frequently as the factor that can deter students from cheating, particularly by continuous reminder that the God is always watching.